Pulmonary thromboemboli in smokers and nonsmokers; Risk factors and anatomic disturbution of emboli in CT angiographies - Mehdi Pishgahi; Leila Zarei; Pegah Mohaghegh; Rama Bozorgmehr (Publisher: Shahid Beheshti University of Medical Sciences, 2019)
Introduction: Recognition of risk factors in different high-risk groups such as smokers in comparison with non-high risk groups would help to develop good preventive strategies for pulmonary thromboemboli (PTE). The purpose of this study was to investigate and compare clinical findings and risk factors in smoker and nonsmoker patients with pulmonary thromboembolism and assessing anatomical variant in pulmonary computerized tomography angiographies.Methods: In this descriptive study 260 consecutive patients suspected to have PTE underwent pulmonary computerized tomography angiographies in a training hospital since 2015 to 2018. Patient with documented PTE were enrolled. Clinical finding and risk factors were determined and compared between them.Results: From 260 patients 172 subjects (66.15%) had PTE and enrolled in the study. Fifty-six (32%) were smoker and 116 (68%) non-smoker. The smoker group was younger and male gender was more predominant. Oxygen saturation and inspired oxygen partial pressure differed between smokers and non-smokers (P < 0.05). The predisposing factors of thromboembolism and anatomic distribution of emboli were the same in smokers and non-smokers.Conclusion: Regarding different factors responsible for PTE in smokers and non-smokers, clinical presentation and anatomic distribution of PTE are comparable.